Shearing bridge bonds in carbon nitride vesicles with enhanced hot carrier utilization for photocatalytic hydrogen production. Issue 13 (5th June 2022) - Liu, Ping; Li, Shisen; Zhang, Lingling; Yin, Xingliang; Ma, Yongchao
Abstract : The synergistic effect of morphology tailoring and the formation of oxygen-containing groups in g-C3 N4 enhanced the production and separation of photoinduced carriers for photocatalytic H2 production. Abstract : Although carbon nitride (g-C3 N4 ) is a common photoconversion material, its photocatalytic activity is constrained by fast carrier recombination and weak light absorption. Here, a precursor reforming strategy is developed to construct melamine precursor rods with an etched surface. After being calcinated, the morphology of the melamine precursor is transformed to interconnected vesicles with open characteristics. In addition, XPS analysis and DFT calculations demonstrate the formation of oxygen-containing groups in the open vesicles, thereby boosting charge separation for surface photocatalytic H2 production. Such a synergistic regulation strategy produces superior visible-light photocatalytic activity (608.3 μmol h −1 g −1 ), and the H2 production rate is 4.43-times higher than that of bulk g-C3 N4 . These findings suggest an accessible way to construct effective photocatalysts via a precursor reforming strategy that can efficiently boost carrier production and spatial separation.